Masalah Kecemasan Siswa Kelas IV SDN Jaka Mulya III dalam Menghadapi Ujian: Faktor Penyebab dan Solusi - Latifah, Azizah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to identify the factors causing anxiety among elementary school students during exams, as well as the solutions provided by teachers. The research was conducted at SDN Jaka Mulya III, involving 25 fourth-grade students. Data were collected through observations, in- depth interviews with students, teachers, and parents, and analysis of students' exam results. The findings revealed that parental pressure was the dominant factor contributing to anxiety, followed by insufficient study preparation, negative perceptions of exams, a competitive classroom environment, and a lack of emotional support. The teacher's solutions included communicative approaches with parents, structured study guidance, relaxation techniques, and creating a collaborative learning environment. This study concludes that addressing student anxiety requires collaboration between teachers, parents, and students.